Simultaneous conversion of methane and methanol into gasoline over bifunctional Ga-, Zn-, In-, and/or Mo-modified ZSM-5 zeolites - Choudhary, Vasant R.; Mondal, Kartick C.; Mulla, Shafeek Abdul Rashid (Angewandte Chemie-International Edition, 2005)
Keywords: gallium; heterogeneuos catalysis; methane activation; Molybdenum; zeolites

Energy-efficient syngas production through, catalytic oxy-methane reforming reactions - Choudhary, Tushar V.; Choudhary, Vasant R. (Angewandte Chemie-International Edition, 2008)
Keywords: fuels; heterogeneous catalysis; methane activation; Partial oxidation; Syngas

MnXWO4 nanostructure-based catalysts for single-step oxidation of cyclohexane and methane to oxygenates - Prabu, Marimuthu; Manikandan, Marimuthu; Samal, Pragnya Paramita; Gurrala, Lakshmi Prasad; Mekala, Siva Prasad; Archana, Ramakrishnan; Nayak, Chandrani; Bhattacharyya, D.; Jha, S. N.; Krishnamurty, Sailaja; Raja, Thirumalaiswamy (ACS Applied Nano Materials, 2023)
Activation of the C-H bond in cyclohexane (CYH) and methane is a crucial step to obtain desirable oxygenated products using nanostructured catalyst and is a great challenge and an efficient route to mitigate the inauspicious effects of climate change. The active sites were identified using XRD, HR-TEM, SEM, N2 sorption analysis, TPR, Raman, XPS, TGA, in situ DRIFT, XAS, etc. In optimal reaction conditions, 46% of CYH was converted into adipic acid (AA) on MnxWO4 nanostructures within 6 h. The recyclability test confirmed the catalyst heterogeneity, which revealed no appreciable loss of catalytic activity even after three consecutive reactions. In situ DRIFT study reveals that CYH is oxidized to cyclohexanone and cyclohexanol (KA oil) and is further oxidized to AA via carboxylate intermediates. DFT studies disclosed that MnOx species are responsible for the C-H activation of CYH, and the Mn2+/Mn3+ redox centers play a vital role in the absorption of KA oil to form AA. Herein, we demonstrated the significant role of the ``MnOx'' species and that adequate Lewis and Bronsted acidic sites, redox centers of (Mn2+/Mn3+), and lattice oxygen are accountable for the CYH conversion toward the AA. Additionally, we have reported the oxidation of methane to methanol (146 mu mole per gram of catalyst) in the presence of water at 75 degrees C without over-oxidation products.
Keywords: Adipic Acid; C-H bond activation; Cyclohexane oxidation; methane activation; MnOx chain; Redox center